2020
DOI: 10.1155/2020/2903542
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Cancer-Related Pain Treatments and Factors Affecting Proper Management in Ayder Comprehensive Specialized Hospital, Mekelle, Ethiopia

Abstract: Background. Cancer-related pain (CRP) is a major problem with a potential negative impact on quality of life of the patients and their caregivers. Purpose. To assess the adequacy of cancer-related pain management in Ayder Comprehensive Specialized Hospital (ACSH). Methodology. A facility-based cross-sectional study design was conducted in ACSH from January to March 2019. A well-structured professional-assisted questionnaire using Brief Pain Inventory-Short Form (BPI-SF) was used to collect data concerning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 24 publications
7
12
5
Order By: Relevance
“…But this study is higher than a study in Libya, 3.87% of patients were associated with poor adherence to guidelines in cancer pain management ( 8 ). On the other hand, this study is lower than a study conducted in a similar setting (UoGCSH) 5 years before (65%) ( 16 ) and Ayder Comprehensive Specialized Hospital (43.95%) ( 18 ) in Ethiopia, in Japan (70%) ( 7 ), and in Punjab, India (77%) ( 9 ). This might be due to the difference in socioeconomic status, the patient's inability to communicate the intensity of his or her pain, and the patient's culture ( 9 ).…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…But this study is higher than a study in Libya, 3.87% of patients were associated with poor adherence to guidelines in cancer pain management ( 8 ). On the other hand, this study is lower than a study conducted in a similar setting (UoGCSH) 5 years before (65%) ( 16 ) and Ayder Comprehensive Specialized Hospital (43.95%) ( 18 ) in Ethiopia, in Japan (70%) ( 7 ), and in Punjab, India (77%) ( 9 ). This might be due to the difference in socioeconomic status, the patient's inability to communicate the intensity of his or her pain, and the patient's culture ( 9 ).…”
Section: Discussioncontrasting
confidence: 65%
“…The sample size for this study is determined using a single population proportion formula by considering the prevalence of 43.95% from the study done in the same setting 5 years ago ( 18 ), 95% CI, 5% margin of error.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is comparable to a previous study in Ethiopia which documented that 80% of non-communicable diseases experience moderate to severe pain [ 26 ]. Other studies in Ethiopia, among patients with chronic diseases, also reported that over three-quarters of them experienced pain [ 27 , 28 ]. The prevalence of pain was very high compared to a study done amongst Portuguese cancer patients [ 19 ], which reported a prevalence of 42%; the pain prevalence was also higher than studies done in other countries: in Japan among cancer patients (66%), [ 22 ], in the UK and Germany among cancer patients (62%), [ 18 ], and in the Czech Republic among patients with chronic diseases including cancer (52%), [ 29 ].…”
Section: Discussionmentioning
confidence: 99%